The Tradition of Western Philosophy of Education: Ancient Philosophy, the Middle Ages, and Modern Education - Ikbal, Muhammad; Sukardi, Ismail; Astuti, Mardiah (The Future of Education Journal, 2024)
This research explores the development of the Western educational philosophy tradition divided into three main eras: ancient, medieval, and modern. In the ancient era, the thought of Plato and Aristotle provided a significant philosophical basis. Plato put forward the concept of the world of ideas as the foundation of reality and the goal of education to form wise leaders, while Aristotle introduced logic and scientific approaches that became the foundation of rational thinking. In the Middle Ages, Thomas Aquinas' thought was dominated by combining Christian theology and Aristotelian philosophy in the academic tradition. This thought emphasizes the harmonization of reason and faith and contributes to the synthesis between religious belief and rationality. The modern era is marked by a paradigm shift through the thought of John Locke, Jean-Jacques Rousseau, and Johann Heinrich Pestalozzi. Locke emphasized the importance of experience in character formation, basing his theory on tabula rasa. Rousseau introduced a natural educational approach that focuses on the development of children according to their nature. Meanwhile, Pestalozzi prioritized morality and intellectuality as the main goals of education. Using a qualitative approach through a literature review, this paper highlights the contribution of each era to the evolution of educational philosophy. The results show that the development of the Western educational philosophy tradition reflects an ongoing effort to understand the relationship between individuals, knowledge, and society, and provides guidance for contemporary educational practice.